2020
DOI: 10.1039/d0sm01448f
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of transport and adhesion of thermogenic nano-carriers in microvessels

Abstract: Externally triggered thermogenic nanoparticles (NPs) are potential drug carriers and heating agents for drug delivery and hyperthermia. A good understanding of transport and adhesion behaviors of NPs in microvessels is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…Although it has long been thought that drug nanocarriers will facilitate cancer therapeutics by directing drugs to solid tumors, nanomedicine development has not yet achieved promising clinical outcomes. Numerous reports indicate that virus-/inorganic nanoparticles-/organic nanoparticles-based nanocarriers could improve the efficacy and safety of anticancer drugs through potential targeting, mitigated drug release in non-target tissues, and pH-sensitive drug release in the tumor microenvironment (TME) [ 4 , 5 , 6 , 7 ]. Tumor vascular permeability and the enhanced permeability and retention (EPR) mechanism in macromolecular drug delivery to solid tumors have been reported as successful strategies for cancer therapeutics [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has long been thought that drug nanocarriers will facilitate cancer therapeutics by directing drugs to solid tumors, nanomedicine development has not yet achieved promising clinical outcomes. Numerous reports indicate that virus-/inorganic nanoparticles-/organic nanoparticles-based nanocarriers could improve the efficacy and safety of anticancer drugs through potential targeting, mitigated drug release in non-target tissues, and pH-sensitive drug release in the tumor microenvironment (TME) [ 4 , 5 , 6 , 7 ]. Tumor vascular permeability and the enhanced permeability and retention (EPR) mechanism in macromolecular drug delivery to solid tumors have been reported as successful strategies for cancer therapeutics [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The particle adhesion at the temperature of 25°C was better than that at 39°C and reached the minimum at 43°C. Our previous simulation work 50 showed that an increase in temperature leads to an increase in the number of NPs attached to the vessel wall when the influence of temperature on the binding of the ligands on NPs to the receptors of endothelial cells is ignored. The reason is that the drag force acting on the particles and the Brownian movement of the particles change greatly with the increase in temperature, leading to a high probability of NP margination to the vessel wall for adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Droplet-based microfluidics has gained widespread attention among researchers for the past two decades, owing to its capability of precise control of minute volumes (Manga 1996;Adamson et al 2006;Baroud, Gallaire & Dangla 2010;Vladisavljević et al 2013;Nozaki et al 2021). Important to mention here is that the paradigm of droplet-based microfluidics has shown significant technical and research potential specifically due to its suitability in point-of-care diagnostics (Shamloo & Hassani-Gangaraj 2020), drug delivery (Yue et al 2020), analysing and screening of bio/chemical reaction products (Zheng & Ismagilov 2005) and many more related areas (Moon et al 2010;Santos et al 2016;Madadelahi, Ghazimirsaeed & Shamloo 2019). Researchers have explored several aspects of droplet behaviour such as droplet generation, breakup (Link et al 2004;Jullien et al 2009;Leshansky & Pismen 2009;Leshansky et al 2012;Hoang et al 2013) and merging/coalescence (Christopher et al 2009), in various microfluidic devices such as a T-junction, flow-focusing junction and co-flowing junction, to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Important to mention here is that the paradigm of droplet-based microfluidics has shown significant technical and research potential specifically due to its suitability in point-of-care diagnostics (Shamloo & Hassani-Gangaraj 2020), drug delivery (Yue et al. 2020), analysing and screening of bio/chemical reaction products (Zheng & Ismagilov 2005) and many more related areas (Moon et al. 2010; Santos et al.…”
Section: Introductionmentioning
confidence: 99%